2023
DOI: 10.51248/.v43i01.1993
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimycotic activity of grapefruit leaf extract on Candida species - An in vitro study

Abstract: Introduction and Aim: Candidiasis is one of the most common pathological conditions affecting the oral mucosa. Synthetic antifungals are being eliminated from the market due to the burden of environmental residues and carcinogenesis. Bioactive phytochemicals such as alkaloids, terpenoids, polyacetylenes, unsaturated isobutylamides, and phenolics are considered safer than synthetic products. The medical field is continuously exploring plant products against the increasing number of antibiotic-resistant organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It showed positive inhibition zones assay results, suggesting good antifungal activity against C. albicans [56, 57] (Table 2). Prasad and colleagues investigated the effect of a grapefruit leaf extract against Candida species [58]. The results showed that this EO extract was more active on C. albicans and C. krusei than the commercially available Amphotericin B [58] (Table 2).…”
Section: Natural Compounds With Anti-candida Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed positive inhibition zones assay results, suggesting good antifungal activity against C. albicans [56, 57] (Table 2). Prasad and colleagues investigated the effect of a grapefruit leaf extract against Candida species [58]. The results showed that this EO extract was more active on C. albicans and C. krusei than the commercially available Amphotericin B [58] (Table 2).…”
Section: Natural Compounds With Anti-candida Activitiesmentioning
confidence: 99%
“…Prasad and colleagues investigated the effect of a grapefruit leaf extract against Candida species [58]. The results showed that this EO extract was more active on C. albicans and C. krusei than the commercially available Amphotericin B [58] (Table 2).…”
Section: Natural Compounds With Anti-candida Activitiesmentioning
confidence: 99%
“…Citrus paradisi, a member of the Rutaceae family, is a perennial species. This plant contains narirutin and naringin, flavanones, ferulic and p-coumaric acids, vanillic, gallic acids phenolic acids, carotenoids, flavonoids, terpenoids, essential oils, and ascorbic acid, which have numerous health benefits due to their pharmacologically active properties (Gupta et al, 2010;Anupama Prasad et al, 2023;Kumar et al, 2020) The work aims to synthesize selenium nanoparticles using an extract from Citrus paradisi plant leaves in an environmentally friendly, cost-effective, and simple approach. The properties of the nanoparticles were characterised, and their antibacterial activities were investigated.…”
mentioning
confidence: 99%